Probing the sun with high resolution - Meeting on "Probing the Sun with High Resolution" (2001 : Udaipur Solar Observatory); Tripathy, S. C.; Venkatakrishnan, P.; Udaipur Solar Observatory (Udaipur, India) (New Delhi : Narosa Pub. House, 2003)
Contributed articles presented at the Meeting on "Probing the Sun with High Resolution" was held on Oct. 10-16, 2001 at Udaipur Solar Observatory, Udaipur.
Includes bibliographical references.
Keywords: Helioseismology -- Congresses; Solar oscillations -- Congresses; Sun -- Observations -- Congresses